Case report: C-reactive protein apheresis in cardiogenic shock: case series from the C-reactive protein apheresis in acute myocardial infarction-registry - Torzewski, J.; Mattecka, S.; Ries, W.; Garlichs, C. D.; Heigl, F.; Fiedler, J.; Sheriff, A. (Frontiers in Drug Discovery, 2023)
C-reactive protein (CRP) apheresis may preserve myocardial tissue after acute myocardial infarction with delayed revascularization. Ten consecutive patients with cardiogenic shock were graded using the Society of Cardiovascular Angiography and Interventions shock classification and treated with CRP apheresis. All patients tolerated CRP apheresis well and were discharged in good clinical condition.